Inmigración y música latina en Barcelona: el papel de la música y el baile en procesos de reafirmación e hibridación cultural - Llano Camacho, Isabel (Sociedad y Economía, 2008)
The arrivals ofpopulation proceeding from Latin America, as well as the internationalization ofthe salsa music have propitiated the transformation ofthe sonorous, cultural and social space of Barcelona during last decade. These factors have helped to develop some processes ofreaffirmation and cultural hybridization that are demonstrated through the analysis ofcertain practices ofconsumption, production and musical reception, like for example going to dance in discotheques, radio’s listening and to attend salsa congresses; things that are analyzed here